مشروعيّة دليل العرف وصلاحيّته لمستجدّات العصر: دراسة في قضايا العادات الجديدة في ظل جائحة كوفيد 19 = The legitimacy of Uruf and its relevance to the developments of modern time: a study on issues related to Covid-19 new normal - Mochammad Sahid, Mualimin; Fettane, Amar; Syed Abdurrahman Al-Yahya, Syed Mohammad Chaedar (Persatuan Kakitangan Akademik Univeriti Sains Islam Malaysia, 2021)
Scholars have agreed on the legality of custom and considering it a Islamic legal proof (dalil) on which the legal rulings are based. Majority of moslem scholars from different schools of thoughts have taken this evidence and considered it a secondary source to be used when determining some of the legal rulings related to what people are familiar with when there is no evidence from the Qur’an, the Sunnah or consensus. Considering custom (uruf) as a source of legislation - in addition to other sources - indicates the capacity of Islamic Sharia and its relevance for every time and place. Despite the development of time, which is accompanied by the developments of life, there is guidance in the Shariah that explains its provisions. This research aims to demonstrate the significance of custom (uruf) evidence in the face of the modern era, which is full of ever-changing and developing life, especially with the practice of new normal due to the Covid-19 pandemic that affects the whole world to this day. The world has been greatly affected by the spread of this pandemic in all aspects of life, and has witnessed changes in various fields of what people described as new habits during and after the pandemic. The research is based on the descriptive analytical method and library research. It attempts to shed light on the status of the custom (uruf) and the extent to which it gives benefits to people when facing the Covid-19 new normal. The study reached some results, the most important of which is that custom (uruf) is the source of Islamic (shariah) legislation that can be applied in facing the developments of the modern era and various issues related to it. The rulings related to the new normal that have emerged due to the Covid-19 pandemic can referred to flexibility and immensity of the evidence of custom (uruf) that emphasizes the interests (masalih) of people in their worldly and hereafter lives.